(3eNJUQ GdcGed aj GdVYaGA dGHf YOi GdLQLGfis - (3Jbi GdOjf GdebQjRis; (3YHO Gddg Hf YOj Hf YHO Gddg Hf eMeO GHf eHGQc Hf GdbWGf GdLQLGfj, CHh CMeO,J (B365 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B82s
Keywords: (3GdJGQjNs